URBAN CHANGE DETECTION BASED ON REMOTE SENSING AND GIS STUDY OF SALEM REVENUE DIVISION, SALEM DISTRICT, TAMIL NADU, INDIA. - Shanmugam TAMILENTHI; Rajagopalan BASKARAN (European Journal of Geography)
Rapid urbanization has significant impact on resources and urban environment. With increased availability and improved quality of multi-spatial and multi-temporal remote sensing data, it is now possible to detect urban changes in a timely and cost-effective way. This study aims to quantify changes in urban area of Salem revenue division, Tamil nadu located in India, using Land sat and IRS-LISS-III image. Urban changes were detected by satellite images of Land sat MSS in 1973, Land sat and IRS-LIS-III in 2010 using a geographic information system (GIS). The settlement area has grown 2.07 times during the past 37 years as a result of industrial development, population growth and permanent migration was the main driving forces for settlement area expansion. According to the results, the extent of urban areas 69.899sqkm and 144.97sqkm in the years 1973 and 2010 respectively.